Vinyl chloride resin composition and electric wire / cable obtained by using the same

The vinyl chloride resin composition with calcium carbonate and zinc stannate additives addresses dispersion issues and hydrogen chloride gas suppression, ensuring high productivity and effective electrical properties.

JP2025008316APending Publication Date: 2025-01-20PROTERIAL LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023110369
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

The dispersion of fine inorganic fillers in vinyl chloride resin compositions is inadequate due to insufficient shear stress during kneading, leading to poor product quality, increased self-heating, and reduced productivity, while adding fillers to suppress hydrogen chloride gas generation during combustion.

Method used

A vinyl chloride resin composition incorporating finely divided calcium carbonate treated with a surface treatment agent and zinc stannate, along with specific amounts of trimellitic acid ester plasticizer, polyester plasticizer, and acrylic polymer, to enhance dispersibility and reduce hydrogen chloride gas emission.

Benefits of technology

The composition achieves high productivity with minimal hydrogen chloride gas generation during combustion, maintaining excellent electrical properties and oil resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008316000004
    Figure 2025008316000004
  • Figure 2025008316000005
    Figure 2025008316000005
  • Figure 2025008316000006
    Figure 2025008316000006
Patent Text Reader

Abstract

To provide a vinyl chloride resin composition for wire coating which has a reduced amount of hydrogen chloride gas in combustion and is excellent in workability, and an electric wire / cable obtained by using the vinyl chloride resin composition as an insulator.SOLUTION: A vinyl chloride resin composition includes: a vinyl chloride resin; a trimellitic acid ester plasticizer; a polyester-based plasticizer; calcium carbonate particles as a hydrogen chloride gas absorber, which are surface-treated with a surface treatment agent; a zinc stannate compound; and an acrylic polymer as a working aid. The vinyl chloride resin composition includes 5 to 15 pts.mass of the zinc stannate compound and 2.5 to 15 pts.mass of the acrylic polymer, with respect to 100 pts.mass of the vinyl chloride resin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a vinyl chloride resin composition and an electric wire / cable using the same. [Background technology]

[0002] Depending on the degree of polymerization of the vinyl chloride monomer (chloroethylene) and the type and amount of plasticizer added, polyvinyl chloride resin products can be used to manufacture products with a variety of physical properties, from rigid polyvinyl chloride resin to flexible polyvinyl chloride resin.

[0003] Furthermore, because polyvinyl chloride resin is inexpensive and can be produced in large quantities, it is used as an industrial resin material in a wide range of industries, including for components and building materials, including electric wires and cables.

[0004] Polyvinyl chloride resin has high flame retardancy and excellent electrical insulation, chemical resistance, water resistance, and colorability, so it has traditionally been used as a base for resin compositions used to make insulators and sheaths (the outer layer of cables) in electric wires and cables.

[0005] However, since polyvinyl chloride resin contains a large amount of chlorine in its structure, it generates harmful hydrogen chloride gas when burned. In recent years, in consideration of the environment, specified values ​​have been set to limit the amount of hydrogen chloride gas generated during combustion to an extremely small amount depending on the application.

[0006] One possible method for suppressing the amount of hydrogen chloride gas generated when polyvinyl chloride resin is burned is to add a large amount of fine inorganic filler to the polyvinyl chloride resin. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2015-225837 A Summary of the Invention [Problem to be solved by the invention]

[0008] When a large amount of fine inorganic filler is added to a polyvinyl chloride resin, if sufficient shear stress is not applied during kneading of the material, the inorganic filler cannot be sufficiently dispersed in the polyvinyl chloride resin composition, resulting in a problem of reduced oil resistance and electrical properties of the product. To solve this problem, it is necessary to increase the shear rate or extend the kneading time in order to increase the shear stress.

[0009] To increase the shear rate, it is necessary to shorten the tip clearance or increase the rotor speed.

[0010] However, if the tip clearance (the distance between the tip of the mixer's rotor and the inner wall of the mixer) is shortened in order to increase the shear rate, the temperature of the material rises during mixing (self-heating). Increasing the rotor speed also creates the problem of self-heating. Therefore, there is a risk that self-heating may cause thermal degradation of the polyvinyl chloride resin during mixing (hydrogen chloride desorption).

[0011] If the kneading time is extended, there is a concern that the productivity of polyvinyl chloride resin products will decrease.

[0012] Therefore, an object of the present invention is to provide a vinyl chloride resin composition which is highly productive and generates a small amount of hydrogen chloride gas upon combustion, and an electric wire / cable using the same. [Means for solving the problem]

[0013] Means for Solving the Problems The present inventors have conducted intensive research aimed at solving the above problems and have found a vinyl chloride resin composition to which target amounts of fine calcium carbonate and zinc stannate can be added.

[0014] A brief outline of a representative embodiment of the present invention will be described below.

[0015] [1] The vinyl chloride resin composition of the present invention comprises a vinyl chloride resin, a trimellitate ester plasticizer, a polyester-based plasticizer, calcium carbonate particles that have been surface-treated with a surface treatment agent as a hydrogen chloride gas absorbent, a zinc stannate compound, and an acrylic polymer as a processing aid; The content of the zinc stannate compound is 5 to 15 parts by mass, and the content of the acrylic polymer is 2.5 to 15 parts by mass, based on 100 parts by mass of the vinyl chloride resin.

[0016] [2] The electric wire of the present invention is an electric wire including a conductor and an insulating layer covering the conductor, the insulating layer comprises a vinyl chloride resin, a trimellitic ester plasticizer, a polyester-based plasticizer, calcium carbonate particles surface-treated with a surface treatment agent as a hydrogen chloride gas absorbent, a zinc stannate compound, and an acrylic polymer as a processing aid; The vinyl chloride resin composition contains 5 to 15 parts by mass of the zinc stannate compound and 2.5 to 15 parts by mass of the acrylic polymer, relative to 100 parts by mass of the vinyl chloride resin.

[0017] [3] The cable of the present invention is a cable including a conductor, an insulating layer covering the conductor, and a covering layer covering the insulating layer, the coating layer comprises a vinyl chloride resin, a trimellitic ester plasticizer, a polyester-based plasticizer, calcium carbonate particles surface-treated with a surface treatment agent as a hydrogen chloride gas absorbent, a zinc stannate compound, and an acrylic polymer as a processing aid; The vinyl chloride resin composition contains 5 to 15 parts by mass of the zinc stannate compound and 2.5 to 15 parts by mass of the acrylic polymer, relative to 100 parts by mass of the vinyl chloride resin. Effect of the Invention

[0018] According to a representative embodiment, the present invention can provide a polyvinyl chloride resin composition which is highly productive and generates a small amount of hydrogen chloride gas upon combustion, and an electric wire / cable using the same. [Brief description of the drawings]

[0019] [Figure 1] 1 is a schematic cross-sectional view of an electric wire according to one embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view of a cable according to an embodiment of the present invention. [Diagram 3] FIG. 1 is a diagram showing a schematic configuration of an extruder used in the examples for carrying out a cable production (extrusion) step. [Figure 4] FIG. 2 is a graph showing the relationship between the torque change and the kneading time for a vinyl chloride resin composition to which no acrylic polymer is added, which is an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, the embodiments will be described in detail with reference to the drawings.

[0021] In the following embodiments, as a general rule, descriptions of identical or similar parts will not be repeated unless particularly necessary.

[0022] <Vinyl chloride resin composition (PVC composition)> According to the embodiment described below, the amount of hydrogen chloride gas generated as measured based on the provisions of JSC7397-4 (method of testing characteristics related to the flammability of electric wires and cables) is 100 mg / g or less, and the volume resistivity at 30°C is 3.0 × 10 13 The vinyl chloride resin composition can be used as a wire covering material.

[0023] [Base: polyvinyl chloride resin] The physical properties of the vinyl chloride resin product in this embodiment can be controlled in a wide range from hard to soft by adjusting the degree of polymerization of the monomer vinyl chloride (chloroethylene) and the type and amount of the plasticizer. In order to provide a vinyl chloride resin composition according to the present invention for use as a wire coating material, which has an appropriate material viscosity and excellent kneading processability and oil resistance, it is preferable to use a vinyl chloride resin with a degree of polymerization of 2000 to 3000 as the base, and more preferably one with a degree of polymerization of about 2500.

[0024] [Processing aid: acrylic polymer] In order for the powdered polyvinyl chloride resin to be quickly kneaded (gelled; hereinafter, sometimes simply referred to as "gelled") in a kneader, an acrylic polymer is added as a processing aid.

[0025] Conventionally, powdered polyvinyl chloride resin is charged into a kneader together with various compounding additives, and is gelled by exposure to shear stress. After that, the compounding additives are distributed into the polyvinyl chloride resin, and a process for dispersing the additives homogeneously by further shear stress is required.

[0026] The addition of an acrylic polymer as a processing aid can shorten the time from when the powdered polyvinyl chloride resin and various compounded additives are charged into the kneader until gelation, thereby shortening the overall kneading time and ensuring that the kneading time required to disperse the various compounded additives within the set kneading time is longer.

[0027] If the amount of the acrylic polymer added is insufficient, the effect of shortening the kneading time will be insufficient, whereas if the amount of the acrylic polymer added is excessive, there is a concern that the tackiness of the vinyl chloride resin composition will increase, which may have an adverse effect on the processability, etc. of the vinyl chloride resin composition.

[0028] The content of the acrylic polymer is preferably from 2.5 to 15 parts by mass, and more preferably from 5 to 10 parts by mass, based on 100 parts by mass of the vinyl chloride resin.

[0029] If the weight average molecular weight of the acrylic polymer is too small, the adhesion of the PVC composition increases, and if the weight average molecular weight of the acrylic polymer is too large, the processability of the PVC composition decreases. The weight average molecular weight of the acrylic polymer used as the processing aid in this embodiment is preferably 200,000 to 300,000, and more preferably about 250,000.

[0030] [Plasticizer: Trimellitic acid ester] In the present invention, trimellitic acid ester is used as a plasticizer not only to avoid the use of phthalic acid esters, which are of concern due to their environmental impact, but also to improve the electrical insulation properties and heat aging resistance of the wire coating material.

[0031] In the present embodiment, the trimellitic acid ester may be, for example, a trimellitic acid tris-2-ethylhexyl ester, a trimellitic acid isononyl ester, or a trimellitic acid mixed linear alkyl ester, and one or a mixture of two or more of these may be used, but is not limited thereto. In view of high plasticization efficiency and excellent economic efficiency, it is preferable to use a trimellitic acid tris-2-ethylhexyl ester as a plasticizer.

[0032] The content of the trimellitic acid ester is preferably 30 to 100 parts by mass based on 100 parts by mass of the vinyl chloride resin.

[0033] [Plasticizer: Polyester plasticizer] There are a wide variety of polyester plasticizers with viscosities of 100 to 10,000 at 25° C. When used as a plasticizer, there are no particular limitations on the viscosity.

[0034] From the viewpoint that wire coating materials are required to suppress the amount of hydrogen chloride gas generated during combustion, to have high oil resistance, and to have high electrical insulation properties, it is preferable to use a plasticizer in the present invention that has a viscosity of 1,000 to 5,000 at 25° C., and it is more preferable to use a plasticizer with a viscosity of about 3,000.

[0035] The plasticizer in the present embodiment may include, but is not limited to, adipic acid polyester, sebacic acid polyester, and aromatic polyester. From the viewpoint of versatility and economy, adipic acid polyester is preferred.

[0036] The content of the polyester plasticizer is preferably 5 to 80 parts by mass with respect to 100 parts by mass of the vinyl chloride resin.

[0037] [Surface-treated calcium carbonate particles] By adding calcium carbonate to polyvinyl chloride resin, it is possible to capture hydrogen chloride gas generated during combustion of polyvinyl chloride resin. In particular, when calcium carbonate fine particles having a particle size of 1.0 μm or less are used, the efficiency of capturing hydrogen chloride gas generated during combustion is higher. In this embodiment, the calcium carbonate fine particles preferably have a particle size of 0.2 μm or more and 1.0 μm or less.

[0038] However, as the particles become smaller, the specific surface area becomes larger and the calcium carbonate particles tend to aggregate with each other. The aggregated calcium carbonate particles reduce the efficiency of capturing hydrogen chloride gas generated during combustion and reduce the oil resistance of a vinyl chloride resin composition containing the aggregated calcium carbonate particles.

[0039] Therefore, the calcium carbonate particles used in the present embodiment are surface-treated with a surface treatment agent to suppress aggregation of the particles.

[0040] As the surface treatment agent for the calcium carbonate particles of the present invention, fatty acids, fatty acid esters obtained by reacting fatty acids with alcohols, and surface treatment agents other than fatty acids can be used as long as they can suppress aggregation of calcium carbonate particles.

[0041] In the present embodiment, examples of fatty acids include medium-chain saturated fatty acids having 6 to 12 carbon atoms, medium-chain unsaturated fatty acids having 6 to 12 carbon atoms, long-chain saturated fatty acids having 13 or more carbon atoms, and long-chain unsaturated fatty acids having 13 or more carbon atoms. The fatty acids are not limited to these.

[0042] Examples of fatty acids include, but are not limited to, stearic acid, lauric acid, palmitic acid, myristic acid, caprylic acid, capric acid, oleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, and docosahexaenoic acid.

[0043] Examples of surface treatment agents other than fatty acids include silane coupling agents.

[0044] The content of the calcium carbonate particles is preferably 30 to 80 parts by mass with respect to 100 parts by mass of the vinyl chloride resin.

[0045] [Zinc stannate compounds] When an appropriate amount of zinc stannate compound is added to vinyl chloride resin, a crust (char) that covers at least a part of the surface of the material being burned is generated during combustion, which makes it possible to suppress combustion and prevent the emission of hydrogen chloride gas generated during combustion. However, when a large amount of zinc stannate compound is added to vinyl chloride resin, the dispersibility of the zinc stannate compound decreases, and the oil resistance of the vinyl chloride resin composition decreases. From the viewpoint of balancing the flame retardancy and the oil resistance, the content of the zinc stannate compound is preferably 5 to 15 parts by mass per 100 parts by mass of vinyl chloride resin.

[0046] Furthermore, from the viewpoint of use as a wire coating material, when a zinc stannate compound containing many hydroxyl groups, such as zinc hydroxystannate, is used, it is preferable to add it in combination with zinc borate to prevent a decrease in the electrical insulation properties of the vinyl chloride resin composition.

[0047] [Other additives] The vinyl chloride resin composition used as the wire covering material may contain antioxidants, insulation improvers, flame retardants, etc. in order to satisfy required properties such as certain mechanical strength and insulating properties.

[0048] (Antioxidants) The antioxidant in the present embodiment is preferably a phenol-based antioxidant. Examples of the phenol-based antioxidant include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (CAS No. 6683-19-8), 2,2'-thiodiethylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (CAS No. 41484-35-9), n-octadecyl 3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate (CAS No. 2082-79-3), octyl-3,5-di-tert-butyl-4-hydroxy-hydrocinnamate (CAS No. 125643-61-0), 2,4-bis[(dodecylthio)methyl]-6-methylphenol (CAS No. 110675-26-8), benzenepropanoic acid, 3-(1,1-dimethylethyl)-4-hydroxy-5-methyl-, 1,2-ethanediylbis(oxy-2,1-ethanediyl)ester (CAS No. 36443-68-2), 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione isocyanuric acid tris(3,5-di-tert-butyl-4-hydroxybenzyl) (CAS No. 27676-62-6), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane (CAS No. 1843-03-4), 4,4'-butylidenebis(6-tert-butyl-m-cresol) (CAS No. 85-60-9), 2,2'-dimethyl-2,2'-(2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diyl)dipropane-1,1'-diyl bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propanoate] (CAS No. 90498-90-1), 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (CAS No. 1709-70-2), 4,4',4'',4''''-methanetetrayltetraphenol tetrakis(4-hydroxyphenyl)methane 4-[tris(4-hydroxyphenyl)methyl]phenol (CAS No.53184-78-4), N,N'-(1,3-propanediyl)bis[3,5-di-tert-butyl-4-hydroxybenzenepropanamide] (CAS No. 69851-61-2), N,N'-(hexane-1,6-diyl)bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propanamide] (CAS No. 23128-74-7), 2-methyl-4,6-bis[(n-octylthio)methyl]phenol (CAS No. 110553-27-0), tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanurate (CAS No. 40601-76-1), benzenepropanoic acid, 3-(1,1-dimethylethyl)-4-hydroxy-5-methyl-, 1,2-ethanediyl bis(oxy-2,1-ethanediyl) ester (CAS No. 36443-68-2), 2,6-di-t-butyl-p-cresol (CAS No. 128-37-0), 3-(3,5-di-tert-butyl-4-hydroxyphenyl)-N'-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propanoyl]propanehydrazide (CAS No. 32687-78-8) bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propanoic acid][oxalylbis(azanediyl)]bis(ethane-2,1-diyl) (CAS No. 70331-94-1).

[0049] The phenolic acid antioxidants may be used alone or in combination of two or more kinds.

[0050] In order to achieve a more excellent antioxidant function, it is more preferable to use it in combination with a sulfur-containing compound such as pentaerythritol tetrakis[3-laurylthiopropionate] (CAS No. 29598-76-3) or ditridecyl 3,3'-thiobispropionate (CAS No. 10595-72-9).

[0051] Furthermore, it is also possible to use the phenol-based antioxidant and the amine-based antioxidant in combination. Amine antioxidants include poly(2,2,4-trimethyl-1,2-dihydroquinoline) (CAS No. 26780-96-1), 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline (CAS No. 91-53-2), reaction product of diphenylamine with acetone (CAS No. 68412-48-6), 1-N-(4-methylpentan-2-yl)-4-N-phenylbenzene-1,4-diamine (CAS No. 793-24-8), N-isopropyl-N'-phenyl-p-phenylenediamine (CAS No. 101-72-4), N,N'-di-2-naphthyl-1,4-phenylenediamine (CAS No. 93-46-9), p-(p-toluenesulfonylamide)diphenylamine (CAS No. 101-72-4), and p-(p-toluenesulfonylamide)diphenylamine (CAS No. 101-72-4). No. 100-93-6), 4,4'-bis(α,α-dimethylbenzyl)diphenylamine (CAS No. 10081-67-1), 4,4'-dioctyldiphenylamine (CAS No. 101-67-7), and N-phenyl-1-naphthylamine (CAS No. 90-30-2).

[0052] More preferably, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (CAS No. 6683-19-8) is used as the phenolic antioxidant.

[0053] There is no particular limitation on the method of addition of the phenolic acid antioxidant or a mixture thereof, such as a master batch in which it is mixed with a resin.

[0054] (Insulation improver) The insulation improver in the present embodiment may be any clay-containing compound, and examples of the insulation improver include the LHM series of Insulite (registered trademark) manufactured by Mizusawa Kagaku Kagaku Co., Ltd. The insulation improver is not limited to this.

[0055] (Flame retardant) In the present embodiment, the flame retardant is preferably an antimony oxide compound having a synergistic effect with the halogen element contained in the polyvinyl chloride resin. Specifically, antimony trioxide and antimony pentoxide can be mentioned, and antimony trioxide is more preferable.

[0056] In addition to the above, other additive components can be blended into the vinyl chloride resin composition as necessary, such as lubricants, surfactants, inorganic or organic fillers, reinforcing agents, bulking agents, crosslinking agents, silicon coupling agents, compatibilizers, copper degradation inhibitors, ultraviolet absorbers, light stabilizers, colorants, etc.

[0057] (Preparation of vinyl chloride resin composition) The vinyl chloride resin composition can be prepared by mixing and melt-kneading the above-described components. Kneading can be performed using a known kneading device, for example, a batch kneader such as a Banbury mixer or a pressure kneader, or a continuous kneader such as a twin-screw extruder.

[0058] The vinyl chloride resin composition obtained as described above has a hydrogen chloride gas generation amount of 100 mg / g or less as specified in JCS 7397-4, and a volume resistivity of 3.0×10 as measured by the volume resistivity test method in accordance with JIS K6723, Section 6.8. 13 It is possible to obtain a vinyl chloride resin composition having properties of Ω·cm or more. By making such a resin composition, it is possible to provide a wire coating material that has excellent electrical properties while suppressing the amount of hydrogen chloride gas generated.

[0059] <Electric wire> The electric wire in the present embodiment has an insulating layer made of the vinyl chloride resin composition. As an example of this electric wire, as shown in Fig. 1, an electric wire 1 in which the outer circumference of a conductor 2 is covered with an insulating layer 3, in which the insulating layer 3 is made of the vinyl chloride resin composition described above, can be exemplified.

[0060] Here, the conductor 2 may be any commonly used metal wire, such as a copper wire, a copper alloy wire, an aluminum wire, a gold wire, or a silver wire. The conductor 2 may be a metal wire plated with a metal such as tin or nickel. The conductor 2 may also be a twisted conductor made by twisting together metal wires.

[0061] Fig. 3 is a diagram showing a schematic configuration of an example of an extruder for producing an electric wire in the present embodiment. As shown in Fig. 3, the extruder 11 includes a cylinder 20, a screw 13 rotatably provided in the cylinder 20, a hopper 12 for supplying a material into the cylinder 20, and a crosshead 16. The extruder 11 also includes a neck 15 between the crosshead 16 and the screw 13, and a breaker plate 14 between the neck 15 and the screw 13. The crosshead 16 has a die 17, and a conductor 18 (conductor 2) passing through the crosshead 16 is covered with an insulating layer in the crosshead 16, passes through the die 17, and is drawn out of the crosshead 16 as an electric wire 19 (electric wire 1).

[0062] <Cable> Also, a single electric wire 1 shown in Fig. 1 can be used or multiple electric wires can be bundled together to form a cable. An example of this cable is a cable 10 in which the outer periphery of a conductor 2 is covered with an insulating layer 3, and the outer periphery of the electric wire is further covered with a covering layer (sheath) 4, as shown in Fig. 2.

[0063] In this cable 10, the insulating layer 3 may be made of any insulating material that is usually used as an insulating layer for electric wires, such as polyvinyl chloride, fluororesin, cross-linked polyethylene, natural rubber, synthetic rubber, etc. Also, this insulating layer 3 may be made of the vinyl chloride resin composition described above.

[0064] The covering layer (sheath) 4 is made of the vinyl chloride resin composition described above. In this case, when bundling a plurality of electric wires, the electric wires are bundled together with the insert, and a pressure winding tape is applied to the outer periphery to form the covering layer (sheath) 4 as the outermost layer.

[0065] As a manufacturing method for this cable, the conductor 2 in the manufacturing method for the electric wire described above is replaced with the electric wire 1, and the cable 10 can be manufactured in a similar manner by using an extruder to cover the outer circumference of the electric wire 1 with the vinyl chloride resin composition described above to form a covering layer (sheath). EXAMPLES

[0066] In the following embodiments, in order to understand the present invention, the vinyl chloride resin composition according to the present invention is used for the wire insulation and cable sheath to produce electric wires and cables. There are no limitations on the type of conductor, structure, interposition, semiconductive layer, restraining winding tape, shield braid, reinforcing layer, or use of the electric wire / cable structure.

[0067] The following describes an embodiment of kneading polyvinyl chloride resin with various additives, preparing a sheet for evaluating the properties of the polyvinyl chloride resin composition, and preparing an electric wire using the polyvinyl chloride resin composition, but the present invention is not limited thereto. The preparation of the electric wire is also one example, and the electric wire (a conductor covered with an insulator) may be extruded to form a cable, and the extrusion conditions, conductor insulator material, and electric wire / cable structure are not limited thereto.

[0068] The internal mixer kneader used in the following examples is given as an example. Other than that, there is no particular limitation as long as it is a commonly used kneading device such as a roll mill, an extruder, a kneader, an autoclave, etc., and there is no limitation on the kneading conditions.

[0069] [Mixing polyvinyl chloride resin with various additives] The polyvinyl chloride resin and various additives were weighed out in the amounts shown in Tables 2 and 3, respectively, and the total amount was adjusted to 229.4 g. The mixture was added to a stainless steel container, heated at 90° C. for 4 hours, and then left at room temperature overnight.

[0070] The polyvinyl chloride resin and various additives were stirred in a stainless steel container and then poured into a 2000 mL capacity mixer kneading tank (hereinafter sometimes referred to as a closed type mixer kneader) with a closed type two-blade rotor that had been preheated to 170°C, and when all the materials were in the tank, the pressure lid was lowered, the rotor speed was set to 30 rpm, and kneading began. After 10 minutes had passed since the start of kneading, the rotor rotation was stopped, the pressure lid was raised, and the kneaded materials were removed from the tank.

[0071] [Preparation of characteristic evaluation sheet] The roll surface temperature of the 6-inch roller was set to 170°C, and the gap between the rolls was set to 1 mm. In order to minimize shearing, the kneaded material was quickly molded into a sheet using the 6-inch roller under the above conditions, and then heated and pressed at 180°C for 5 minutes using a press molding machine to obtain a 1 mm thick sheet for evaluating properties.

[0072] [Making electric wires] The obtained sheet for property evaluation was processed by the 6-inch roller to obtain 4 mm square pellets. The 4 mm square pellets were fed into a single-screw extruder, and a vinyl chloride resin composition was extruded onto the conductor under the conditions shown in Table 1 to produce an electric wire.

[0073] In this embodiment, a conductor having a thickness of 1.25 SQ was used, which was made by twisting together a plurality of tin-plated soft copper wires, and the conductor was covered with an insulator of a vinyl chloride resin composition having a thickness of 0.78 mm by extrusion.

[0074] Table 2 shows Examples 1 to 5 and Comparative Examples 1 to 3, and Table 3 shows Examples 6 to 7 and Comparative Examples 4 to 5, respectively.

[0075] <Evaluation> Moreover, the vinyl chloride resin composition, vinyl chloride resin sheet, and electric wire 1 obtained in each example were evaluated for the following properties, and the results are shown in FIG.

[0076] [Composition processability (kneadability) test] The maximum torque value was considered to be the point at which the polyvinyl chloride resin was kneaded in the kneader, and the time it took for the polyvinyl chloride resin to go from a powder state to being kneaded in the kneader was used as an index of kneadability.

[0077] The kneading torque value was recorded over time from the start of kneading in the internal mixer kneader, and the torque peak time (the time from the start of kneading until the maximum torque value) was measured.

[0078] The change in torque depending on the kneading time for the formulation of Comparative Example 1, that is, the formulation without adding an acrylic polymer, is shown in Figure 4. Using Comparative Example 1 as a base, the shortening rate of the torque peak time for each of the Comparative Examples and Examples in which an acrylic polymer was added was calculated using the following calculation formula 1, and a shortening rate of 60% or more was deemed to have sufficiently improved kneading properties and was passed (marked with ◎ in Tables 2 to 3), a shortening rate of 30% or more was deemed to have improved kneading properties and was passed (marked with ○ in Tables 2 to 3), and a shortening rate of less than 30% was deemed to have insufficient improvement in kneading properties and was failed (marked with × in Tables 2 to 3).

[0079] (Formula 1) Torque peak time reduction rate (%) = {(BA) / B} x 100 A: Torque peak time (s) for each example and comparative example B: Torque peak time (s) for Comparative Example 1 (acrylic polymer not added) [Evaluation test of hydrogen chloride gas generation amount] A hydrogen chloride gas generation test was conducted based on the provisions of JCS 7397-4. The sheet for characteristic evaluation was cut into approximately 1 mm squares, and 0.5 g of the cut sheet for characteristic evaluation was placed in a heating tube and burned at 800°C for 30 minutes. The gas generated during combustion was collected, and the amount of hydrogen chloride gas contained in the gas was quantified using a quantitative titration method.

[0080] A more detailed explanation is as follows.

[0081] According to JCS 7397-4, section 4.4.3, five gas absorption tubes (without filters) filled with 50 mL of water were connected together to capture the generated hydrogen chloride gas. 250 mL of the collected water and 50 mL of water used to wash each absorption tube were placed in an Erlenmeyer flask, along with a titration reagent (iron and silver ion reagents) and isoamyl alcohol, and titration was performed with ammonium thiocyanate. Ammonium thiocyanate was added and stirred, and the end point was when coloration (coloring to red due to the generation of iron thiocyanate) continued for 3 seconds. The test was performed once (n=1), and the amount of hydrogen chloride gas generated per unit amount of vinyl chloride resin composition was calculated using the following formula 2.

[0082] (Formula 2) Hydrogen chloride gas generation amount (mg / g) = 3.65 (BA) x (300 / 50) / C A: The amount of ammonium thiocyanate titrated in the gas generated by burning the sheet for characterization (mL) B: Ammonium thiocyanate titration amount (mL) when baking empty (without sample) C: Fee for preparing sheets for sex evaluation (g) The samples with hydrogen chloride gas generation of 100 mg / g or less were judged as passing (marked with ◯ in Tables 2 to 3), and the samples with hydrogen chloride gas generation exceeding 100 mg / g were judged as failing (marked with × in Tables 2 to 3).

[0083] [Electrical test (volume resistivity evaluation)] The volume resistivity of the characteristic evaluation sheet was evaluated as an index of applicability to a wire covering material.

[0084] Specifically, a DC voltage of 500 V was applied to the characteristic evaluation sheet in a thermostatic chamber set at 30°C, and after 1 minute, the current value of the characteristic evaluation sheet was measured using an ultra-high insulation resistance measuring instrument R3840A (manufactured by ADVABTEST) to calculate the volume resistivity of the characteristic evaluation sheet.

[0085] Considering the applicability to wire coating materials, the volume resistivity of the characteristic evaluation sheet was set at 3.0×10 13 Those with a volume resistivity of 3.0×10 Ω·cm or more are considered to be passed (marked with a circle in Tables 2 to 3). 13Those with a resistivity of less than Ω·cm were deemed to have failed (marked with an × in Tables 2 to 3).

[0086] [Tensile test (evaluation of tensile properties)] The characteristic evaluation sheet was shaped into a No. 2 dumbbell test piece as specified in JIS K6723, and pulled at a speed of 200 mm / min using a Tensilon type small tensile testing machine STA-1225 (manufactured by Orientec Co., Ltd.). The tensile strength was calculated from the tensile load at break and the cross-sectional area of ​​the dumbbell test piece using the following calculation formula 3.

[0087] The test was performed three times (n=3), and the average value of the three results was calculated.

[0088] (Formula 3) Tensile strength (MPa) = tensile load at break (N) / cross-sectional area of ​​dumbbell test piece (mm 2 ) [Oil resistance test] The characteristic evaluation sheet, which was shaped like a dumbbell test piece No. 2 as described in JIS K6723, was immersed for 4 hours in test oil (IRM902 oil: manufactured by Nippon San Oil) heated to 85°C. After that, the test oil adhering to the surface was wiped off and the specimen was left at room temperature for 24 hours, and then pulled under the same conditions as the tensile test (speed of 200 mm / min), and the tensile strength was calculated from the tensile load at break and the cross-sectional area of ​​the dumbbell test piece using the above-mentioned formula 3.

[0089] The test was performed three times (n=3), and the average value of the three results was calculated.

[0090] The tensile strength before and after immersion in the test oil was calculated and the tensile strength retention was calculated using the following calculation formula 4.

[0091] (Formula 4) Tensile strength retention rate (%) = (tensile strength after immersion in test oil (MPa) / tensile strength before immersion in test oil (MPa)) x 100% The sheets for evaluation of the characteristics had a tensile strength retention rate of 80% or more, which was judged to be pass (marked with an O in Tables 2 to 3), and the sheets for evaluation of the characteristics had a tensile strength retention rate of less than 80%, which was judged to be fail (marked with an X in Tables 2 to 3).

[0092] [Adhesion test] The vinyl chloride resin composition was used to evaluate the tackiness as an index of the stability of the material supply in the production of electric wires. The vinyl chloride resin composition was charged into a hopper, and the state was observed when it was supplied to an extruder.

[0093] Materials that could supply the materials put into the hopper to the extruder without any problems were judged to pass (marked with ◎ in Tables 2 to 3), materials that showed some blocking between materials but were judged not to cause any major problems in terms of impact on workability were judged to pass (marked with ○ in Tables 2 to 3), and materials that were judged to have accumulated in the extruder hopper, causing unstable supply to the extruder and causing serious concerns in terms of impact on workability were judged to fail (marked with × in Tables 2 to 3).

[0094] [Table 1]

[0095] [Table 2]

[0096] [Table 3]

[0097] As shown in Tables 2 and 3, the resin compositions in each example were prepared as follows.

[0098] (Examples 1 to 7) Polyvinyl chloride resin ( *1 100 parts by mass of TH-2500 (soft use) manufactured by Taiyo Vinyl Corporation, trioctyl trimellitate ( *2 Kao Corporation, Trimex T-08A) 50 parts by mass, polyester plasticizer ( *3 10 or 50 parts by mass of ADEKA Cizer PN1030 (viscosity 3000 MPa·s at 25°C), acrylic polymer ( *4 2.5 to 15 parts by mass of Metablen P-570A (manufactured by Mitsubishi Chemical Corporation) and a phenolic compound ( *5SONGWON's Songnox1010) 0.5 parts by mass, antimony trioxide ( *6 Twinkling Star Co., Ltd.) 9.8 parts by mass, and a clay-containing compound ( *7 Insulite (registered trademark LHM-103HP) manufactured by Mizusawa Chemical Industries, Ltd.) 0.5 parts by mass, Ca-Zn composite stabilizer ( *8 Mixture of fatty acid calcium and fatty acid zinc) 4 parts by mass, zinc stannate ( *9 5 to 15 parts by mass of Alkanex (registered trademark ZS) manufactured by Mizusawa Chemical Industries, Ltd., calcium carbonate ( *10 A resin composition was obtained by kneading 50 parts by mass of Lighton 32X (average particle size 0.7 μm, surface treatment agent: fatty acid) manufactured by Bihoku Funka Kogyo Co., Ltd.

[0099] (Comparative Examples 1 to 5) Polyvinyl chloride resin ( *1 100 parts by mass of TH-2500 (soft use) manufactured by Taiyo Vinyl Corporation, trioctyl trimellitate ( *2 Kao Corporation, Trimex T-08A) 50 parts by mass, polyester plasticizer ( *3 10 or 50 parts by mass of ADEKA Cizer PN1030 (viscosity 3000 MPa·s at 25°C), acrylic polymer ( *4 Mitsubishi Chemical Corporation's Metablen P-570A) at 0, 2, 10, and 20 parts by mass, and a phenolic compound ( *5 SONGWON's Songnox1010) 0.5 parts by mass, antimony trioxide ( *6 Twinkling Star Co., Ltd.) 9.8 parts by mass, and a clay-containing compound ( *7 Insulite (registered trademark LHM-103HP) manufactured by Mizusawa Chemical Industries, Ltd.) 0.5 parts by mass, Ca-Zn composite stabilizer ( *8 Mixture of fatty acid calcium and fatty acid zinc) 4 parts by mass, zinc stannate ( *9 2.5 and 20 parts by mass of Alkanex (registered trademark ZS, manufactured by Mizusawa Chemical Industries, Ltd.), calcium carbonate ( *10 A resin composition was obtained by kneading 50 parts by mass of Lighton 32X (average particle size 0.7 μm, surface treatment agent: fatty acid) manufactured by Bihoku Funka Kogyo Co., Ltd.

[0100] According to the method described in the <Evaluation> column above, the evaluation items are kneadability when kneaded in a closed mixer kneader, amount of hydrogen chloride generated during combustion, oil resistance (retention of tensile strength before and after immersion in test oil), electrical properties (volume resistivity), and adhesion. If the product passes all items overall, it is judged as passing, and if it fails even one item, it is judged as failing.

[0101] The vinyl chloride resin compositions prepared according to the formulations shown in Examples 1 to 7 were evaluated for their kneadability when kneaded in a closed mixer kneader, and for various properties evaluated using evaluation sheets prepared using the vinyl chloride resin compositions. It was confirmed that all targets were met, and no problems were observed in terms of adhesion during the preparation of electric wires, or in the overall workability, similar to the work of extrusion coating with a normal vinyl chloride resin composition.

[0102] As shown in Table 2, Comparative Example 1, in which no acrylic polymer was added as a processing aid, failed the electrical properties and oil resistance. From this result, it is considered that when the torque peak time is long, it takes a long time for the vinyl chloride resin to be kneaded, so that various additives are not sufficiently dispersed in the vinyl chloride resin, thereby deteriorating the electrical properties and oil resistance of the vinyl chloride resin composition.

[0103] In Comparative Example 2, in which 2 parts by mass of an acrylic polymer was added as a processing aid to 100 parts by mass of the vinyl chloride resin composition, the torque peak time reduction rate was 24.6% compared to Comparative Example 1, and it was found that the kneading property during kneading and the oil resistance property (tensile strength retention rate) did not meet their respective targets. This is thought to be because, although the addition of the acrylic polymer tends to improve the kneading property, the dispersibility of various additives remains insufficient.

[0104] On the other hand, in Comparative Example 3, in which 20 parts by mass of an acrylic polymer was added, the adhesiveness of the material increased, and blocking occurred between the materials themselves and between the materials and the inner wall of the hopper during wire production, making the amount of material supplied to the extruder unstable.

[0105] It was found that Comparative Example 4, in which 20 parts by mass of zinc stannate was added to 100 parts by mass of the vinyl chloride resin composition, did not satisfy the requirements for oil resistance. When the cross section of the vinyl chloride resin composition evaluation sheet of Comparative Example 4 was observed, agglomerates of zinc stannate were observed on the cross section. It is presumed that the excessive addition of zinc stannate caused unnecessary dispersion in the vinyl chloride resin, resulting in a decrease in oil resistance.

[0106] It was found that the amount of hydrogen chloride gas generated during combustion in Comparative Example 5, in which 2.5 parts by mass of zinc stannate was added, did not reach the target. It is believed that when the amount of zinc stannate added is too small, it is difficult to form a sufficient amount of char on the surface of the vinyl chloride resin composition during combustion, and the generated hydrogen chloride gas is released outside the composition.

[0107] The present invention is not limited in any way to the vinyl chloride resin or compounded additives used in the above examples. The shape of the electric wire made of a conductor and a coating material (insulator) as prepared in this example is also not limited, and it can also be used as a cable shape in which the vinyl chloride resin composition of the present invention is coated as a sheath (outer layer) around the outer periphery of the insulator. In that case, the material of the insulating inner layer may be the vinyl chloride resin composition of the present invention, or another resin composition or rubber composition.

[0108] Although the present invention has been described with reference to the above-mentioned embodiment and examples, the present invention is not limited to the above-mentioned embodiment and examples, and various modifications can be made without departing from the spirit and scope of the present invention. [Industrial Applicability]

[0109] The present invention is applicable to wires and cables. [Explanation of symbols]

[0110] 1 electric wire 2 Conductors 3. Insulation layer 4. Covering layer (sheath) 10 Cable 11 Extruder 12 Hopper 13 Screw 14 Breaker plate 15 Neck 16 Crosshead 17 Dice 18 Conductor 19 Electric wire 20 cylinders

Claims

1. The present invention comprises a vinyl chloride resin, a trimellitic ester plasticizer, a polyester plasticizer, calcium carbonate particles that have been surface-treated with a surface treatment agent as a hydrogen chloride gas absorbent, a zinc stannate compound, and an acrylic polymer as a processing aid; The vinyl chloride resin composition comprises 5 to 15 parts by mass of the zinc stannate compound and 2.5 to 15 parts by mass of the acrylic polymer, relative to 100 parts by mass of the vinyl chloride resin.

2. 2. The vinyl chloride resin composition according to claim 1, wherein the weight average molecular weight of the acrylic polymer is 200,000 to 300,000.

3. 2. The vinyl chloride resin composition according to claim 1, comprising 5 to 10 parts by mass of the acrylic polymer relative to 100 parts by mass of the vinyl chloride resin.

4. 2. The vinyl chloride resin composition according to claim 1, wherein the acrylic polymer is trimellitic acid tris-2-ethylhexyl ester.

5. The vinyl chloride resin composition according to claim 1 , wherein the polyester plasticizer is an adipic acid-based polyester.

6. 2. The vinyl chloride resin composition according to claim 1, wherein the degree of polymerization of the vinyl chloride resin is 2,000 to 3,000.

7. 2. The vinyl chloride resin composition according to claim 1, further comprising a phenolic compound as an antioxidant, a clay-containing compound as an insulation improver, and an antimony oxide compound as a flame retardant.

8. The vinyl chloride resin composition according to claim 1, wherein the amount of hydrogen chloride gas generated upon combustion is 100 mg / g or less according to the provisions of JSC 7397-4, and the volume resistivity according to JIS K6723, Section 6.8 is 3.0 × 10 13 The vinyl chloride resin composition has a hardness of Ω·cm or more.

9. The vinyl chloride resin composition according to claim 1, A vinyl chloride resin composition for use in covering electric wires or cables.

10. An electric wire comprising a conductor and an insulating layer coated around the conductor, the insulating layer comprises a vinyl chloride resin, a trimellitic ester plasticizer, a polyester-based plasticizer, calcium carbonate particles surface-treated with a surface treatment agent as a hydrogen chloride gas absorbent, a zinc stannate compound, and an acrylic polymer as a processing aid; The electric wire is composed of a vinyl chloride resin composition containing 5 to 15 parts by mass of the zinc stannate compound and 2.5 to 15 parts by mass of the acrylic polymer, relative to 100 parts by mass of the vinyl chloride resin.

11. A cable comprising a conductor, an insulating layer coated around the conductor, and a coating layer coated around the insulating layer, the coating layer comprises a vinyl chloride resin, a trimellitic ester plasticizer, a polyester-based plasticizer, calcium carbonate particles surface-treated with a surface treatment agent as a hydrogen chloride gas absorbent, a zinc stannate compound, and an acrylic polymer as a processing aid; A cable composed of a vinyl chloride resin composition containing 5 to 15 parts by mass of the zinc stannate compound and 2.5 to 15 parts by mass of the acrylic polymer, relative to 100 parts by mass of the vinyl chloride resin.

Citation Information

Patent Citations

  • Insulated wire

    JP2015225837A